Registros de representação semiótica mobilizados na obtenção do volume de um cilindro: uma atividade orientada pelos princípios da modelagem matemática - Corrêa, Janaina da Silva (2017)
The present research aims to investigate if and how students from the Mathematics Undergraduate course of the Federal University of Santa Maria (UFSM) mobilize semiotic representations when teaching the concept of fuel volume in a cylinder through three activities consisting of 10 items, based on assumptions from mathematics modelling. For this, the theoretical background is based on the register of semiotic representation theory by Duval (2003, 2004, 2011, 2012), mathematical modelling by Biembengut and Hein (2003) and, as a methodological approach, studies on quantitative research by Lüdke and André (1986). From the data production and analysis, it is possible to conclude that activities based on assumptions of mathematic modelling enable the mobilization and the approaching of different registers of semiotics representation, as well as an investigative attitude of the participants. The developed actions have allowed the undergraduate students to teach using the coordinating register process of representation from the same mathematical object, highlighting their knowledge acquisition, necessary in order to understand the different cylinder volume characteristics.